Is There a Role for IgA/C3 Ratio in IgA Nephropathy Prognosis? An Outcome Analysis on An European Population (Iranian Journal of Kidney Diseases, 2020)
Introduction. Serum immunoglobulin A (IgA)/C3 ratio has been reported as a predictor of histological lesions and prognosis in asian patients with IgA nephropathy (IgAN). Since its validity in other populations is unclear, we aimed to evaluate the relationship between IgA/C3 ratio and renal outcome in Caucasian European patients with biopsy-proven IgAN. Methods. We conducted a retrospective, observational study on 95 patients with primary IgAN patients diagnosed between 2010 to 2017 (70% male, age 41 (34 to 49) years, eGFR 39.4 (25.2 to 56.5) mL/ min, proteinuria 1.7 (0.8 to 3.0) g/g). The primary study composite end-point was doubling of serum creatinine, ESRD (dialysis or renal transplant) or death, whichever came first. Results. Median follow-up was 30 (95% CI: 27.5 to 32.4) months; 11% developed ESRD, 10% experienced serum creatinine doubling, and 1% died. The endpoint was reached by 21% of the patients. They had lower eGFR, higher proteinuria and hematuria, and lower serum albumin. The distribution in Oxford classes was alike. The AUROC for IgA/C3 ratio was 0.60 (95% CI: 0.45 to 0.74) and generated an optimal cut-off of 2.91 (sensitivity 68%, specificity 55%). The mean event-free survival of the whole cohort was 5.2 (95% CI: 4.7 to 5.8) years. Patients with IgA/C3 ratio < 2.9 had a tendency to better renal survival (P > .05). In Cox proportional hazard ratio model, the independent predictors of a poorer eventfree survival were higher serum creatinine, higher proteinuria and increased IgA/C3 ratio, while renin angiotensin system inhibitors predicted better outcome. Conclusion. Our study reports evidence that supports IgA/C3 ratio as a reasonable predictor of IgAN prognosis in European patients.